Keabsahan Akta Pengalihan Piutang (Cessie Sebagian) yang Digunakan Cedent untuk Memohon Pailit Cessus - Indriyani Anhar, Hanifah (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2024)
This research aims to examine the validity of the deed of transfer of receivables (partial cessie) used by the cedent to file for cessus bankruptcy. The research method used is normative legal research with a normative juridical approach, statutory approach, and conceptual approach. Empirical legal research methods are also applied through interviews with notaries to strengthen the research results. The research focuses on the validity of the deed of transfer of receivables, using a conceptual approach to analyze legal issues from the point of view of legal concepts and values contained in relevant regulations. Primary legal materials involved the Civil Procedure Code, the Bankruptcy and Debt Payment Obligation Delay Law (PKPU), the Notary Office Law, and the Law on General Courts. The results show that partial cessie, although not yet positively regulated, has legal validity as long as it fulfills the provisions of Article 613 of the Civil Code. Therefore, the partial cessie deed used by the cedent to apply for cessus bankruptcy can be considered valid with the fulfillment of applicable legal requirements.